Lotus-leaf-like structured heparin-conjugated poly(L-lactide-co-epsilon-caprolactone) as a blood compatible material - Lim, Jin Ik; Kim, Seung Il; Kim, Soo Hyun (ELSEVIER, 2013)
A heparin-conjugated biodegradable polymer was synthesized by direct coupling of heparin to poly(L-lactide-co-e-caprolactone) (PLCL) and was manufactured into lotus-leaf-like structured films. We evaluated whether lotus-leaf-like structured heparin-conjugated PLCL (LH-PLCL) could be applied to blood vessel tissue engineering. Differences in the surface structures of the films with respect to hydrophobicity and the lotus effect as well as the antithrombotic efficiency in human whole blood were examined using scanning electron microscopy (SEM) and a contact angle meter. Recovery testing was conducted using a tensile strength testing machine, and quantitative analysis of conjugated heparin was performed using the toluidine blue calorimetric method. The concentration of conjugated heparin was 0.14 mu g/mg H-PLCL, and the contact angle with the lotus-leaf-like surface was approximately 1200. Furthermore, the LH-PLCL film yielded a lower platelet adhesion rate (around less than 1.4%) in whole blood than that yielded by an untreated PLCL film. These results indicate a unique property of bound heparin and the lotus-leaf-like structure. This novel LH-PLCL polymer could be applied as a blood/tissue compatible biodegradable material for implantable medical devices and tissue engineering. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: SURFACE MODIFICATION; SUPERHYDROPHOBIC SURFACE; CONTROLLED-RELEASE; DESIGN; TISSUE; CREATION; FILM